Willingness to Accept, Willingness to Pay, and Loss Aversion - Jonathan Chapman; Mark Dean; Pietro Ortoleva; Erik Snowberg; Colin Camerer (Center for Economic Studies and ifo Institute (CESifo), 2023)
We use four incentivized representative surveys to study the endowment effect for lotteries in 4,000 U.S. adults. We replicate the standard finding of an endowment effect–the divergence between Willingness to Accept (WTA) and Willingness to Pay (WTP), but document three new findings. First, we find little evidence that the endowment effect is related to loss aversion for risky prospects, counter to predictions of popular theories in economics. Second, WTA and WTP not only diverge, but are, at best, weakly correlated. Third, WTA and WTP strongly relate to other aspects of risk preferences. The structure of these behaviors points to different theories of the endowment effect.
Keywords: C90; D81; D91; 330; Willingness To Pay; Willingness to Accept; endowment effect; loss aversion; Zahlungsbereitschaftsanalyse; Risikoaversion; Glücksspiel; Besitztumseffekt